Improving Students' Mathematical Literacy Skills Through the Application of Genially in the PBL Model - Vina Apriatni; Dedi Nurjamil; Eko Yulianto (PRISMA, 2026)
The purpose of this study was to determine the improvement of students' mathematical literacy skills through the application of genially on problem-based learning (PBL) model. This research was conducted at SMA Negeri 6 Garut. The research method used was quasi experimental with pretest-posttest control group design. The experimental class was given treatment by applying genially to the problem-based learning (PBL) model while the control class was given the problem-based learning (PBL) model only. The population in this research were all students of class X, with a sample of two classes namely class X 12 as the experimental class and class X 4 as the control class. sampling based on the random assignment technique. The data collection techniques used were observation, unstructured interview, and mathematical literacy test. The instruments used were student mathematical literacy test. The data analysis technique used the Two Independent Samples Test. Based on the results of data analysis, it can be concluded that there is an increase in students' mathematical literacy skills through the application of Genially in the Problem Based Learning (PBL) model with a significance of 0.03.